DEVELOPMENT OF THE ACTIVITIES OF NON-GOVERNMENTAL ORGANISATIONS OF THE DISABLED IN THE CONTEXT OF SOCIAL INTEGRATION - BENEŠEVIČIŪTĖ, Irmina (Socialinė teorija, empirija, politika ir praktika, 2015)
The paper analyses the development of the activities of non-governmental organisations of the disabled in the context of social integration. Social Integration Act (2013) emphasizes that during the implementation of social integration ideas, it is important to ensure equal rights and opportunities of the disabled in the society, to establish the principles of their social integration, to define social integration system and its prerequisites as well as the authorities implementing the social integration of people with disabilities. The NGO concept of social integration of people with disabilities in Lithuania is described presenting a variety of social integration concepts assumed by scientists, theorists and practitioners. Hereby is presented an empiric investigation, which purpose was to reveal the approach and experience of respondents towards the development of the NGOs activities. The findings of a qualitative research performed by the author of the article revealed that disabled people expected the most social services from the NGOs. The independence of disabled people is pursued by social services. Educational peculiarities are also characteristic to the activities of NGOs. The research findings demonstrated that the disabled, who joined NGOs, expressed their need for training and developing their self-expression. Analysing the experiences of respondents, it became clear that the need for material help was important to disabled people. The research showed that usually NGOs represented a group of disabled people. The more disabled people were represented, the more they integrated to the society itself. Talking about the forms of representation, the participants of the research emphasised that the representatives of authorities transferred to NGOs to solve the problems of disabled people. This demonstrated the trust in NGOs by people, who form a particular social policy, and the people, who implement it, whereas such organisations were more able to solve the problems of disabled people than state institutions. Applying qualitative research methods, the research helped to reveal the difficulties arising from the administration of NGOs and people forming and implementing the social policy representing the interests of disabled people. Difficulties limiting the social integration of disabled people were established: the bureaucracy of the representatives of the state authorities in respect of NGOs, the lack of public awareness of disabled people, too strict requirements of disabled people to the representatives of the authorities, and the transfer of conflicts to disabled people. These difficulties showed the lack of dialogue by all participants. The participants of the research actualised the factors, which were oriented towards the changes of the development of NGOs’ activities, pursuing the social integration of disabled people. The representation of interests oriented towards the activeness of disabled people in the NGOs gaining the influence on the resolutions of authorities, the ability of disabled people to cooperate in NGOs pursuing the high quality representation of their interests, financial support for a person representing and solving personal problems, the representation of interests oriented towards decision-making by the members of NGOs, closer relationships with the representatives of the authorities, efficient organisation of the NGOs’ activities, and NGOs as a measure to overcome the social exclusion of disabled people were listed as the important endeavours of NGOs. Hence, an NGO is a social overcoming tool, which encourages higher involvement into society through the participation of disabled people in the activities of NGOs.